The Effectiveness Of Leaflet Media On Maternal Knowledge And Attitudes About Stunting Prevention At Titi Papan Village Medan Deli District In 2025 - Marlina, Marlina; Sembiring, Elya Rosa Br; Pratiwi, Debby; Siahaan, May Frinsiska (Jurnal Maternitas Kebidanan, 2025)
Health promotion media has a meaningful relationship in increasing public knowledge and attitudes. One of the health promotion media is leaflet media. Leaflets are sheets of paper containing health messages pictures and writing about a health topic that is conveyed to the audience or reader. Based on initial survey data in Titi Papan Village, Medan Deli District, the number of stunted toddlers in 2021 was 33 cases. Titi Papan Village had the highest stunting with 24 cases of toddlers, Mabar Village 5 cases, and Mabar Hilir Village 3 cases. The purpose of this study was to determine the effectiveness of leaflet media on mothers' knowledge and attitudes about stunting prevention in Titi Papan Village, Medan Deli District. This study used a quasi-experimental design with a pretest-posttest design. The population of this study were pregnant women and mothers who had babies aged 0-2 years as many as 124. The sample in the study was 94 respondents, using the Slovin formula, the analysis used univariate and bivariate with Paired T-test. The results of the study showed a variable of changes in respondent knowledge before and after counseling with a significant level of p = 0.001 and a change in respondent attitudes before and after counseling with a significant level of p = 0.000 regarding stunting prevention in Titi Papan Village, Medan Deli District. This study concludes that there is effectiveness of leaflet media on mothers' knowledge and attitudes about stunting prevention in Titi Papan Village, Medan Deli District.